Subsidizing national champions: an evolutionary perspective - Cécile Aubert; Oliver Falck; Stephan Heblich (Center for Economic Studies and ifo Institute (CESifo), 2008)
A national-champions-related industrial policy has become (again) en vogue among European politicians. Against this background, our work orders different types of national champions along the industry lifecycle. Different types of locally bound externalities appear along the lifecycle. In a simple model, we show that it may be efficient to subsidize innovative firms in their early stages or to protect mature firms from competition to appropriate these externalities. However, non-benevolent politicians may not choose efficient policies. Real-world examples indicate that politicians tend to concentrate on externalities at the mature stage of the lifecycle. These externalities may be transitory or at the expense of foreign country consumers.
Keywords: L52; O25; O33; P11; 330; National champions; industrial policy; industry lifecycle; externalities; Industriepolitik; Großunternehmen; Subvention; Unternehmensentwicklung; Innovation; Lebenszyklus; Externer Effekt; Theorie; EU-Staaten